Mind the gap – industry perceptions about postgraduate studies in the discipline of design - van Zyl, H. M. (South African Journal of Higher Education, 2024)
There has been slow uptake and growth in the local postgraduate student numbers in design, especially at the doctoral level. The question must be asked why, especially when looking at the growth of design as a discipline and a widening domain resulting from technological and social development. This study aims to explore industry perceptions about postgraduate studies in design to see if that could be a reason for the slow growth. The study starts with the background of the development of the design discipline, design education, and design research. An analysis of postgraduate graduate numbers over the last decade and current providers provides a context and general landscape. The analysis is followed by a report where the perceptions and attitudes of industry practitioners about postgraduate studies in communication/graphic design were qualitatively explored. The fieldwork comprised in-depth interviews that were conducted with communication designers at various points along their career paths. Three elements were explored: identification of the type of advanced knowledge needs in industry; how design professionals see postgraduate studies, their career paths, and vision for the future; and if postgraduate studies feature in their vision for the future. Some of the participants had previously attempted postgraduate studies and were not successful; their experiences added to the rich data. The research contributes to a better understanding of the reasons for the low postgraduate numbers, and the gap between industry and academia at postgraduate levels is confirmed. The study insights provide the possibilities of increasing postgraduate capacity in design by reducing the gap when designing suitable curricula.